Chemical and enzymatic incorporation of N2-(p-n-butylphenyl)-2'-deoxyguanosine into an oligodeoxyribonucleotide. - Misra, H K (1992)
An 18mer oligodeoxyribonucleotide containing a N2-(p-n-butylphenyl)-2'-deoxyguanosine (BuPdG) residue at the 3' end has been synthesized by both chemical and enzymatic methods. Chemical synthesis involved attachment of 5'-DMT-BuPdG as the 3'-H-phosphonate to uridine-controlled pore glass (CPG), followed by extension via H-phosphonate chemistry. After oxidation of the backbone, deprotection of bases, and removal from CPG, the uridine residue was removed by periodate cleavage and beta-elimination. The resulting oligomer 3'-phosphate was digested with alkaline phosphatase to give the free BuPdG-18mer. E.coli DNA polymerase I (Klenow) incorporated BuPdGTP at the 3' end of the corresponding 17mer primer annealed to a complementary 29mer template, and the properties of this product were identical to those of chemically synthesized BuPdG-18mer. E.coli DNA polymerase I (Klenow) was unable to extend the BuPdG-18mer, and the 3' to 5' exonuclease activity of the enzyme was unable to remove the modified nucleotide.